Produção e utilização de silagens de peixe na nutrição do pacu (Piaractus mesopotamicus) - Vidotti, Rose Meire [UNESP] (2001)
Three types of raw materials (commercial waste from salt water (SW) and freshwater fish (FW); and tilapia filleting residue) were used to produce fish silage by acid digestion (2% formic acid and 2% sulfuric acid), and anaerobic fermentation, (5% of Lactobacillus plantarum and 15% sugar cane molasses). Six test diets were prepared for digestibility trials as follows: 70% reference diet and 30% silage. These diets were fed to juvenile pacu (146 g average weight) in triplicate. Fish were kept in 500-l tanks and feces collected by manual extrusion. It was observed for both processes that saltwater fish waste always presented the highest moisture content and lowest fat and ash. Highest crude protein levels were displayed in silages from commercial fish waste (SW and FW), made from whole fish unfit for human consumption. However, apparent digestibility coefficients did not vary among diets (P>0.05). Although values did not differ statistically, fermented silage consistently displayed higher digestibility coefficients compared to acid silage. The silages exhibited good protein digestibility (72,5 - 80,0%), thus suggesting the feasibility of using fish industry by-products in aquaculture feeds